ANALISIS ALTERNATIF PENEMPATAN SATELIT LAPAN A2 DI ORBIT - Nizam Ahmad (Jurnal Sains Dirgantara, 2010)
The preliminary orbit design of LAPAN A2 satellite takes an assumption that the satellite will be launched on October, 2011. This design used a scenario of satellite placement in orbit at altitude of about 650km, 800 km and 870 km and inclinations of 8, 10 and 20. The orbit analysis shows that if the satellite will be launched in Sriharikota, India, it will be only possible for inclination of 20. A satellite at an altitude of 800 km is more effective for a remote sensing mission than that of 650 km and 870 km, because it will pass Indonesia region 14 times a day with the total swath width is 4205.75 km and time in view is about 11 minutes. In addition, the satellite will revolve the earth 14 times a day with the periode of about 100.85 minutes. Keywords: Satellite, Orbit